Domain‐Size‐Dependent Residual Stress Governs the Phase‐Transition and Photoluminescence Behavior of Methylammonium Lead Iodide. (11th February 2021) - Lee, Kwang Jae; Turedi, Bekir; Giugni, Andrea; Lintangpradipto, Muhammad Naufal; Zhumekenov, Ayan A.; Alsalloum, Abdullah Y.; Min, Jung‐Hong; Dursun, Ibrahim; Naphade, Rounak; Mitra, Somak; Roqan, Iman S.; Ooi, Boon S.; et al.
Abstract: Methylammonium lead iodide (MAPbI3 ) perovskite has garnered significant interest as a versatile material for optoelectronic applications. The temperature‐dependent photoluminescence (TDPL) and phase‐transition behaviors revealed in previous studies have become standard indicators of defects, stability, charge carrier dynamics, and device performance. However, published reports abound with examples of irregular photoluminescence and phase‐transition phenomena that are difficult to reconcile, posing major challenges in the correlation of those properties with the actual material state or with the subsequent device performance. In this paper, a unifying explanation for the seemingly inconsistent TDPL and phase‐transition (orthorhombic‐to‐tetragonal) characteristics observed for MAPbI3 is presented. By investigating MAPbI3 perovskites with varying crystalline states, ranging from polycrystal to highly oriented crystal as well as single‐crystals, key features in the TDPL and phase‐transition behaviors are identified that are related to the extent of crystal domain‐size‐dependent residual stress and stem from the considerable volume difference (Δ V ≈ 4.5%) between the primitive unit cells of the orthorhombic (at 80 K) and tetragonal phases (at 300 K) of MAPbI3 . This fundamental connection is essential for understanding the photophysics and material processing of soft perovskites. Abstract : Domain‐size‐dependent residual stress governs the phase‐transition and photoluminescence behavior of methylammonium lead iodide (MAPbI3 ) perovskite. Key features in the temperature‐dependent photoluminescence and phase‐transition behaviors are related to the extent of crystal domain‐size‐dependent residual stress and stem from the considerable volume difference (Δ V ≈ 4.5%) between the primitive unit cells of the orthorhombic (at 80 K) and tetragonal phases (at 300 K) of MAPbI3 .